ANALISIS STRUKTUR, PERILAKU DAN KINERJA PERBANKAN INDONESIA TAHUN 2004-2012 (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2015)
The structure of the market will have an impact on the behavior and performance of an industry. This study aims 1) to determine the level of market concentration in the banking industry in Indonesia in the year 2004 to 2012; 2) to identify the structure, behavior and performance of the banking industry in Indonesia in the year 2004 to 2012. Models of analysis in this research is descriptive analysis. The sample was selected by purposive sampling with criteria 6 top bank by total assets, based on credit, and by third-party funds. The results showed that the banking industry market concentration level above 50 percent. The market structure of the banking industry is oligopoly with the dominant state banks that make less competitive rivalry.